Pterostilbene‐induced changes in gut microbiota composition in relation to obesity. Issue 1 (3rd August 2016) - Etxeberria, Usune; Hijona, Elizabeth; Aguirre, Leixuri; Milagro, Fermin I.; Bujanda, Luis; Rimando, Agnes M.; Martínez, José Alfredo; Portillo, María P.
Abstract : The anti‐obesity effects exerted by pterostilbene supplementation in Zucker ( fa / fa ) rats, can be associated with the modifications produced by the phenolic compound in gut microbiota composition. These changes are mainly characterized by a reduction in Gammaproteobacteria and an induction of Verrucomicrobia phylum, particularly due to an increase in Akkermansia muciniphila, and the enhancement of Odoribacter splanchnicus bacterial species. Abstract : Scope: Nutritional interventions based on the use of natural bioactive compounds might offer new possibilities for reshaping obesity‐associated bacterial dysregulation or dysbiosis and improving health. We evaluated whether pterostilbene supplementation could induce changes in gut microbiota composition and whether these modifications were associated with improvements in metabolic variables. Methods and results: Zucker ( fa/fa ) rats were given a standard diet supplemented ( n = 10) or not ( n = 9) with pterostilbene (15 mg/kg body weight/day) by oral gavage for 6 weeks. Faucal samples at the beginning and at the end of the intervention period were analyzed by Illumina Mi‐Seq sequencing approach. Pterostilbene exerted protective antiobesity effects, improved metabolic function (insulin sensitivity), and induced structural changes in gut microbiota composition. A decrease in the levels of Firmicutes and an increase in Verrucomicrobia phyla were detected in the pterostilbene‐treated group. Bacterial species belonging to genera Akkermansia and Odoribacter were also increased. A strong inverse correlation between Akkermansia muciniphila and body weight was evidenced. Odoribacter splanchnicus showed a negative correlation with adiposity. Conclusion: Pterostilbene modifies intestinal bacteria composition toward a healthier microbial profile and suggests that the antiobesity effects induced in Zucker rats could be associated with an enrichment of the mucin‐degrading bacterial members, namely Akkermansia and Odoribacter genus.